MANAJEMEN PENDIDIKAN KRISTEN: SEKTOR KAJIAN, PELUANG, DAN PENGEMBANGAN [CHRISTIAN EDUCATIONAL MANAGEMENT: SECTORS OF STUDY, OPPORTUNITIES, AND DEVELOPMENT] - Nasib Tua Lumban Gaol (Polyglot, 2020)
Christian educational management is a new field which was born in Indonesia, particularly, at the Institut Agama Kristen Negeri Tarutung. Its origins can be traced to the year 2018 after the oldest public Christian higher education institution established the field as a new department in the Faculty of Christian Education Science, IAKN Tarutung. The department is expected to contribute to the development and improvement of the quality of managing Christian educational institutions. Consequently, the purpose of this paper is to explore the sectors, opportunities, and development of Christian educational management in the Indonesian context. This study found three sectors of Christian education management starting from the lowest level to the highest, namely the micro, meso, and macro sectors. The field of Christian educational management can be further advanced because the Indonesian government had issued several regulations to enhance the quality of Christian education institutions through various policies. Besides, education stakeholders and researchers may give serious attention the study of Christian educational management so that each Christian education institution can carry out its functions effectively and efficiently.BAHASA INDONESIA ABSTRACT: Manajemen pendidikan Kristen merupakan sebuahbidang keilmuan baru yang dilahirkan di Indonesia, khususnya di Institut Agama Kristen Negeri Tarutung. Asal-usul bidang tersebut dapat ditemukan pada tahun 2018 setelah salah satu lembaga pendidikan Kristen negeri tertua itu mendirikan bidang tersebut sebagai sebuah program studi baru di Fakultas Ilmu Pendidikan Kristen, IAKN Tarutung. Program studi ini diharapkan dapat berkontribusi dalam pengembangan dan peningkatan kualitas pengelolaan lembaga pendidikan Kristen. Oleh karena itu, tujuan dari studi ini adalah untuk mengeksplorasi berbagai sektor, peluang, dan pengembangan pendidikan Kristen dalam konteks Indonesia. Studi ini menemukan tiga sektor manajemen pendidikan Kristen mulai dari level terendah sampai tertinggi, yaitu sektor mikro, meso, dan makro. Bidang manajemen pendidikan Kristen dapat lebih maju di masa mendatang karena pemerintah telah mengeluarkan beberapa regulasi terkait peningkatan lembaga pendidikan Kristen melalui berbagai kebijakan. Selain itu, para pemangku kepentingan dan peneliti dalam bidang pendidikan boleh memberikan perhatiaan serius terkait kajian manajemen pendidikan Kristen supaya setiap lembaga pendidikan Kristen dapat menjalankan fungsinya secara efektif dan efisien.